The Yin and Yang of High-density Lipoprotein and Atherosclerotic Cardiovascular Disease: Focusing on Functionality and Cholesterol Efflux to Reframe the HDL Hypothesis - Ganjali, Shiva; Watts, Gerald F; Banach, Maciej; Reiner, Željko; Nachtigal, Petr; Sahebkar, Amirhossein (Current medicinal chemistry, 2021)
The inverse relationship between low plasma high-density lipoprotein cholesterol (HDL-C) concentrations and increased risk of Atherosclerotic Cardiovascular Disease (ASCVD) is well-known. However, plasma HDL-C concentrations are highly variable in subjects with ASCVD. In clinical outcome trials, pharmacotherapies that increase HDL-C concentrations are not associated with a reduction in ASCVD events. A causal relationship between HDL-C and ASCVD has also been questioned by Mendelian randomization studies and genome-wide association studies of genetic variants associated with plasma HDL-C concentrations. The U-shaped association between plasma HDL-C concentrations and mortality observed in several epidemiological studies implicates both low and very high plasma HDL-C concentrations in the etiology of ASCVD and non- ASCVD mortality. These data do not collectively support a causal association between HDL-C and ASCVD risk. Therefore, the hypothesis concerning the association between HDL and ASCVD has shifted from focus on plasma concentrations to the concept of functionality, in particular cellular cholesterol efflux and HDL holoparticle transport. In this review, we focus on these new concepts and provide a new framework for understanding and testing the role of HDL in ASCVD.
Keywords: kardiovaskulární nemoci; ateroskleróza; Cholesterol; Humans; cholesterol; HDL-cholesterol; lidé; Atherosclerosis; Genome-Wide Association Study; Cardiovascular Diseases; celogenomová asociační studie; Cholesterol, HDL